2020
DOI: 10.21203/rs.3.rs-35019/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of COVID-19 in high burden countries for HIV/TB: A systematic review of evidence

Abstract: Background The triple burden of COVID-19, tuberculosis and human immunodeficiency virus is one of the major global health challenges of the 21 st century. In high burden HIV/TB countries, the spread of COVID-19 among people living with HIV is a well-founded concern. A thorough understanding of HIV/TB and COVID-19 pandemics is important as the three diseases interact. This may clarify HIV/TB/COVID-19 as a newly related field and play an important role in the present and future management of the co-infections. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This is consistent with findings in other studies including high TB post-mortem diagnostic in SSA [43, 44]. Referring to a meta-analysis showing that TB exposure was in the high-risk COVID-19 group (OR 1.67, 95% CI 1.06–2.65) [8]. COVID-19/TB clinical diagnostic may be underestimated in SSA as post-mortem TB diagnostic has shown a high mortality rate.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is consistent with findings in other studies including high TB post-mortem diagnostic in SSA [43, 44]. Referring to a meta-analysis showing that TB exposure was in the high-risk COVID-19 group (OR 1.67, 95% CI 1.06–2.65) [8]. COVID-19/TB clinical diagnostic may be underestimated in SSA as post-mortem TB diagnostic has shown a high mortality rate.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, COVID-19 is associated with other co-morbidities in patients with previous or current pulmonary tuberculosis (PTB) [8]. A recent review found that PTB is a risk factor for COVID-19 regardless of HIV status, both in terms of severity and mortality [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients in this study had pulmonary TB, an opportunistic illness linked to AIDS that raises the probability of hospital admission for people with COVID-19 infection and lengthens stays in the critical care unit. Patients with TB lung disease or HIV-related immunosuppression may be predisposed to severe COVID-19 [7]. This study shows that HIV remains a signi cant risk factor for acquiring SARS-CoV-2 and is associated with a higher risk of COVID-19 infection-related mortality.…”
Section: Discussionmentioning
confidence: 69%